Analisis Perbandingan Implementasi Push Notification Menggunakan Native Web Push API dan Firebase Cloud Messaging (FCM) pada Aplikasi Sipama di SMP Al Akbar - Mohammad Laily Nova Krisna (Fakultas Ilmu Komputer, 2026)
The Student Progress Reporting Information System (SIPAMA), a Progressive Web App (PWA) at SMP Al Akbar, requires a push notification feature to optimize real-time information delivery to parents. This study aims to integrate and compare the performance of Native Web Push API and Firebase Cloud Messaging (FCM). The method employed is experimental-quantitative, testing 2,000 automated notification samples equally distributed in foreground and background conditions , alongside 30 samples for evaluating device resource usage via Chrome Task Manager. The results show that both technologies achieved a perfect 100% delivery rate. In the foreground condition, the Native Web Push API was more responsive with a median latency of 237 ms compared to FCM at 261 ms. In the background condition, FCM's median latency was slightly superior (152 ms) compared to Native Web Push (159 ms). However, pure Native Web Push is vulnerable to background OS throttling, triggering a maximum latency spike of up to 106,800 ms. In terms of efficiency, Native Web Push outperformed FCM under background conditions with lower memory consumption (66.29 MB vs 68.11 MB) and a lighter peak CPU workload (0.51% vs 0.82%). This study concludes that Native Web Push API is recommended for an efficient, pure PWA architecture for parents' devices , while FCM remains relevant if background delivery stability on Android devices is the primary priority.
:: Finalisasi file repositori 5 Agustus 2026_Kurnadi
Keywords: Progressive Web App; SIPAMA; Push Notification; Native Web Push API; Firebase Cloud Messaging